Analysis of environmental financial reporting in the Spanish toll roads sector. Issue 4 (2nd October 2019) - Acerete, Basilio; Gasca, Mar; Llena, Fernando
ABSTRACT: There is a great variety of environmental financial reporting as regards content, extension and how it is included in the annual accounts. Spain and, in particular, the toll roads sector was amongst the first to be required to disclose environmental information. These concessionaires have also been affected by changes in domestic and international accounting regulation. The first objective of the paper is to analyse the quality of environmental financial reporting in the Spanish toll roads sector and its evolution after International Financial Reporting Standards (IFRS) implementation. The second is to compare the reporting behaviour of concessionaires with that of their parent companies. The third is to test what institutional mechanisms influence environmental disclosure. Content analysis has been applied for the period 1999–2015. Results show a minimum environmental reporting level focused merely on complying with regulation requirements, without a useful content revealing the integration of environmental issues into the companies' management. The implementation of IFRS has not improved environmental disclosure and, in some cases, has even worsened it. In addition, under institutional theory, results show that some institutional factors (regulation and sub-sector) explain the environmental financial reporting behaviour of the companies analysed.